Indexing, fiscal lags and inflation - Canavese, Alfredo J.; Heymann, Daniel (Estudios Económicos de El Colegio de México, 1991)
This paper analyzes the dynamics of a model in which prices have inertia and, at the same time, inflation depends also on the fiscal deficit.